2006
DOI: 10.1021/ja056278e
|View full text |Cite
|
Sign up to set email alerts
|

Surface Tailoring for Controlled Protein Adsorption:  Effect of Topography at the Nanometer Scale and Chemistry

Abstract: Protein adsorption behavior is at the heart of many of today's research fields including biotechnology and materials science. With understanding of protein-surface interactions, control over the conformation and orientation of immobilized species may ultimately allow tailor-made surfaces to be generated. In this contribution protein-surface interactions have been examined with particular focus on surface curvature with and without surface chemistry effects. Silica spheres with diameters in the range 15-165 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
662
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 725 publications
(697 citation statements)
references
References 32 publications
32
662
2
1
Order By: Relevance
“…By doing this, the contact area between substrate and protein is increased assuring adsorption. This theory accords well with the findings by Rasmusson et al [21] and Roach et al [30] for the adsorption of HPF on polymer nanostructures and silica nanospheres, for example. The dependence of the orientation of the proteins on the ripple wavelength can be explained as follows.…”
Section: Protein Adsorptionsupporting
confidence: 93%
“…By doing this, the contact area between substrate and protein is increased assuring adsorption. This theory accords well with the findings by Rasmusson et al [21] and Roach et al [30] for the adsorption of HPF on polymer nanostructures and silica nanospheres, for example. The dependence of the orientation of the proteins on the ripple wavelength can be explained as follows.…”
Section: Protein Adsorptionsupporting
confidence: 93%
“…The large loss of adsorbed material from the rough surfaces supports our view that the pores were not penetrated by the protein solution as internal protein would not be removed very easily by flow. Reduced binding strength has previously been reported for BSA on high curvature surfaces 24 .…”
Section: Resultsmentioning
confidence: 68%
“…It has previously been reported that proteins and peptides are affected by nano-structures of similar size to those used here 24,32,33 .…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…13 Protein adsorption on nanoparticles can be affected by the high surface curvature of the particles. [14][15][16][17] Much attention was paid to the question to what extent the structure of proteins is perturbed by adsorption onto hydrophilic or hydrophobic nanoparticles, [17][18][19] or if the interaction with their strongly curved surface can promote aggregation and brillation of proteins. 20,21 On the other hand, it is also possible that the adsorption of the protein causes bridging of two or more nanoparticles.…”
Section: Introductionmentioning
confidence: 99%